Enhancing Social Accountability in Medical Education and Accreditation: A Meeting Report - Larche CL; Kennel M; Tackett S; Marsh DC; Cameron E (Advances in Medical Education and Practice)
Cynthia L Larche,1 Maxwell Kennel,1 Sean Tackett,2 David C Marsh,3– 5 Erin Cameron1,6 1Gilles Arcand Centre for Health Equity, Human Sciences Division, Northern Ontario School of Medicine University, Sudbury, Ontario, Canada; 2Division of General Internal Medicine, Johns Hopkins Bayview Medical Center, Baltimore, Maryland, USA; 3Clinical Sciences Division, Northern Ontario School of Medicine University, Sudbury, Ontario, Canada; 4Health Sciences North Research Institute, Sudbury, Ontario, Canada; 5ICES North, Sudbury, Ontario, Canada; 6Human Sciences Division, Northern Ontario School of Medicine University, Thunder Bay, Ontario, CanadaCorrespondence: Erin Cameron, Northern Ontario School of Medicine University, Thunder Bay, Ontario, Canada, Email ercameron@nosm.caAbstract: Accreditation in medical education stands in need of more empirical grounding. There is a paucity of accreditation research that hinders both quality assurance efforts and the introduction of innovative new approaches to accreditation, such as social accountability standards. The International Social Accountability and Accreditation Steering Committee (ISAASC) was established to address this gap. This meeting report outlines the outcomes of a workshop led by members of the ISAASC to identify research priorities related to social accountability and accreditation. The workshop was held during the International Congress on Academic Medicine (ICAM) on April 13, 2024, in Vancouver, British Columbia and used a modified nominal group technique. Four main priorities were identified, namely that there is a need to: 1) integrate various constituencies in accreditation research, 2) identify global drivers of social accountability standards, 3) measure impacts of socially accountable healthcare education, and 4) develop evaluation tools for accreditation activities.Keywords: accreditation research, medical education, social accountability